Konvergensi Finansial Syariah: Sinergi Emas, Inklusi Digital, dan Ketahanan Sosial-Ekonomi dalam Praktik Pegadaian Syariah: (Islamic Financial Convergence: Gold Synergies, Digital Inclusion, and Socio-Economic Resilience in Islamic Pawnshop Practices) - Zainuddin, Moch; Andriani, Andriani; Amrul Mutaqin (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2025)
Abstract: This study aims to analyze the role of Pegadaian Syariah as a gold bank in promoting asset diversification, monetary stability, and digital financial inclusion in Indonesia, while examining their impact on community economic resilience. The research employs a descriptive qualitative approach with interdisciplinary analysis, combining literature review, field surveys, and policy analysis. Pegadaian Syariah, as a gold bank, offer innovative solutions to enhance economic resilience amidst exchange rate fluctuations. Findings indicate that Gold Bank products, such as gold savings and instalment plans, help communities mitigate inflation risks, with 72% of respondents considering gold as a stable long-term investment. Data analysis reveals that 65% of respondents prefer gold over cash due to concerns about exchange rate volatility. Digital services from Sharia Pawnshops improve accessibility with an 80% satisfaction rate, although digital literacy remains a challenge. The study concludes that Sharia-based Gold Banks effectively strengthen economic stability through asset diversification and digital financial inclusion. These findings recommend enhancing financial education and inter-institutional collaboration to optimize benefits. The research makes significant contributions to developing inclusive financial models in developing countries. Abstrak: Penelitian ini bertujuan menganalisis peran Pegadaian Syariah sebagai Bank Emas dalam mendorong diversifikasi aset, stabilitas moneter, dan inklusi keuangan digital di Indonesia, serta mengkaji dampaknya terhadap ketahanan ekonomi masyarakat. Penelitian menggunakan pendekatan kualitatif deskriptif dengan analisis interdisipliner yang menggabungkan kajian literatur, survei lapangan, dan analisis kebijakan. Pegadaian Syariah sebagai Bank Emas menawarkan solusi inovatif untuk meningkatkan ketahanan ekonomi di tengah fluktuasi nilai tukar. Hasil penelitian menunjukkan bahwa produk Bank Emas seperti tabungan dan cicil emas membantu masyarakat mengurangi risiko inflasi, dengan 72% responden menganggap emas sebagai investasi jangka panjang yang stabil. Analisis data mengungkap 65% responden lebih memilih emas daripada uang tunai karena kekhawatiran terhadap fluktuasi nilai tukar. Layanan digital Pegadaian Syariah meningkatkan aksesibilitas dengan tingkat kepuasan 80%, meski literasi digital masih menjadi tantangan. Bank Emas berbasis syariah terbukti efektif dalam memperkuat stabilitas ekonomi melalui diversifikasi aset dan inklusi keuangan digital. Temuan ini merekomendasikan penguatan edukasi finansial dan kolaborasi antar lembaga untuk optimalisasi manfaat. Penelitian memberikan kontribusi penting bagi pengembangan model keuangan inklusif di negara berkembang.